MENGKAJI FAKTOR-FAKTOR YANG MENYEBABKAN BUTA AKSARA AL-QUR’AN DAN LANGKAH-LANGKAH UNTUK PEMBEBASANNYA - Mutia Sari; Dimas Assyakurrohim; Karoma Karoma; Mardiah Astuti (CV. ADIBA AISHA AMIRA, 2023)
This paper aims to discuss and analyze the factors that cause Al-Qur'an illiteracy and the steps to liberate it. Al-Qur'an is the holy book revealed by Allah SWT to be a life guide for Muslims. On the other hand, the Al-Qur'an is also a blessing for the entire universe, so that its contents are always appropriate and can be used as a guide for human life anytime and anywhere. Al-Qur'an is not only the pages that are read, but must always be understood and practiced, it's just that you need to know that reading the Al-Qur'an also has a practice that gets rewards for its readers. Therefore, besides understanding the Qur'an, learning to read the Qur'an is also very important, or what is referred to in this paper as eradicating Al-Qur'an illiteracy. The eradication of Koran illiteracy has actually become a national program for the Indonesian people. However, the program on a national scale does not seem to have achieved satisfactory results. This is shown by the tests carried out on 3,111 Muslims, where 72.25% were categorized as unable to read the Al-Qur'an properly. In fact, coaching on reading and writing Al-Qur'an has been going on for a long time, but these efforts have not been able to touch people's awareness to learn to read Al-Qur'an. The Koran teacher coaching activities seem less exciting for the community. The problems that will be presented in this paper will discuss the factors that cause many people to be illiterate in the Qur'an, and alternative educational efforts as liberation from illiteracy in the Qur'an which is expected to provide solutions for the community so that they can continue reading and writing activities Al-Qur'an.